(untitled) (Asian Journal of Social Science Studies, 2022)
The flood in Zhejiang in 1922 led to numbers of disaster victims. In the case of insufficient government relief, non-governmental organizations had become the main force in disaster relief, and in the process of disaster relief, a new model had gradually formed with relief fundraising as the core and various small and medium-sized organizations united around it. Under this model, the disaster relief process and results showed many different characteristics from the past and set a typical model for future charitable relief movements.